TECHNO-ECONOMIC ANALYSIS OF BOILER WASTE HEAT-BASED BIOMASS DRYING SYSTEM OF A COAL COFIRING POWER PLANT - Baisir, Mahpudi; Surjosatyo, Adi; Dafiqurrohman, Hafif (Jurnal Rekayasa Mesin, 2024)
This research aims to find the optimal operating pattern in a rotary dryer type biomass drying system with the heating medium from exhaust gas leaving the boiler. This heating medium is believed to provide high profits because it does not require additional energy. However, the lowest moisture may not necessarily provide maximum investment profits due to trade-offs with capital and operational costs. The research results show that the test point at a biomass inlet flow of 10 t/h, a residence time of 25 minutes, and an exhaust gas flow of 90 t/h can optimally obtain the highest three investment parameters, including USD 8,518,085.33 for NPV, 150.32% for IRR, and 0.67 years for PBP. So that it succeeds in reducing the biomass moisture from 44.57% to 10.90%. Reductions in energy output and operational duration should be avoided wherever possible because they have a significant impact on reducing profit.